The Role of Parents in Building Resilience in Early Childhood - Pradini, Susanthi; Nopiana, Nopiana; Fatmawati, Nia (Journal of Early Childhood Education (JECE), 2024)
This research is motivated by the readiness of individuals to adjust to various conditions and challenges faced. For example, during the pandemic conditions we have experienced, This pandemic condition forces individuals to adapt to conditions, including Indonesian families. This condition is also experienced by a person when dealing with unexpected disaster conditions. Many parents find it difficult to deal with their anxiety with all the pressure and keep their children safe. But as time goes by, individuals generally strive to rise from adversity and try to readjust. This ability to rise from depressed situation is called resilience. Resilience grows and develops throughout human life and begins to develop from early childhood. Everyone has different resilience abilities depending on the individual's experience and personality. In children, one of the factors that can play a role in the formation of resilience is the condition of the child's nearest and smallest environment, namely the family and parents. How much effort parents make to create a sense of security and comfort for the family, and the ability of parents to face obstacles is one of the factors that play a role in the formation of children's resilience. This study aims to find out how big the role of parental resilience plays in the formation of resilience in early childhood. The method in this study is a quantitative approach with a correlation technique. The sample was selected using a simple random sampling technique under the criteria of parents who have children aged 2 to 6 years. The result of this study is that parental resilience has a significant role in efforts to build resilience in early childhood (r = 0.487). However, there are still other factors or variables that can play a role in the formation of early childhood resilience need further studies.